PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE, OPINION SHOPPING, KUALITAS AUDIT, DAN AUDIT CLIENT TENURE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN AUDITING - Panggah Wira Angkasa; Dewi Indriasih; Baihaqi Fanani (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2018)
The Impact of Good Governance, Opinion Shopping, Quality Audit and Audit Client Tenure Application towards Going Concern Opinion Audit Acceptance (Empirical Studies on Infrastructure Services Company, Utility, and Transportation which Registered at Indonesian Stock Exchange (ISE) during 2013 – 2017 Period). Essay. Tegal: Economic & Business Faculty, Pancasakti University Tegal. 2018. The aim of this research is to finding out the impact of institutional ownership, independent commissioner, committee audit, opinion shopping, quality audit, audit client tenure towards going concern’s opinion audit on infrastructure services company, utility, and transportation which registered at ISE during 2013 – 2017 period. The population in this research are infrastructure services company, utility, and transportation which registered at ISE during 2013 – 2017 period and the sample determination by using purposive sampling method, so within the result obtained 15 company’s samples. The data analysis method used is logistic regression analysis. Based on logistic regression analytic, the research result concluded that institutional ownership (0,109), audit committee (0,429), opinion shopping (0,607), and quality audit (0,998) are not affecting the going concern opinion audit. Meanwhile, the independent commissioner (0,006), and audit client tenure (0,004) are affecting the going concern opinion audit. Keywords: going concern, opinion audit, institutional ownership, independent commissioner, committee audit, opinion shopping, quality audit, audit client tenure